Detection of cytomegalovirus in upper gastrointestinal biopsies from heart transplant recipients: comparison of light microscopy, immunocytochemistry, in situ hybridisation, and nested PCR. Issue 11 (November 1998) - Muir, S W; Murray, J; Farquharson, M A; Wheatley, D J; McPhaden, A R
Abstract : AIM: To establish the diagnostic value of in situ hybridisation and the nested polymerase chain reaction (PCR) in detecting clinically relevant cytomegalovirus (CMV) infection in upper gastrointestinal biopsies from heart transplant patients. METHODS: Test sensitivity and specificity for detection of CMV early gene RNA by in situ hybridisation and CMV intermediate early gene by PCR were established and then compared with haematoxylin and eosin (H&E) and immunocytochemical detection of CMV in order to establish the best pathological diagnostic approach. All investigations were carried out on formalin fixed, paraffin embedded tissue. RESULTS: Nested PCR had the highest test sensitivity, followed by in situ hybridisation and immunocytochemistry with the same sensitivity; H&E had the lowest. H&E and immunocytochemistry were the most specific but both had a significant false negative rate which was less of a problem with PCR. However, PCR gave no other diagnostic information, and in situ hybridisation was no better than immunocytochemistry. Both in situ hybridisation and PCR were technically complex and more expensive. CONCLUSIONS: H&E and immunocytochemistry represent the best initial screen for CMV and other diseases in upper gastrointestinal biopsies from heart transplant patients. If H&E and immunocytochemistry were negative, nested PCR could significantly increase the diagnostic yield of clinically relevant CMV infection. In situ hybridisation appeared to have no advantages and some drawbacks compared with immunocytochemistry and PCR.